Analisis Sosio-Pragmatik Terhadap Pujian Dan Respon Pujian Pada Masyarakat Suku Saluan - Syahrianti M. Nawir; Nurlaela Nurlaela (LLDIKTI Wilayah IX Sulawesi, 2019)
This research aimed at describing the topics of compliment, the strategies in responding compliment and the influence of intimacy in complimenting among Saluanese in Nambo sub district. This research was conducted in Nambo sub district, Banggai regency. The study was descriptive research by using qualitative approach. Methods used in collecting data were an observation, an interview, and field notes. There were 31 expressions of compliments and compliment respenses used by Saluanese in Nambo sub district. The result of this research indicates that the most topics used by Saluanese in complimenting were possession about 39%, then appearance 32%, performance 26% and personality 3%. It indicates that Saluanese tends to give compliment in possessive aspect such as children, assets, luxury and position or profession. The most strategy used by Saluanese was agreement about 71%, then non-agreement 26% and other interpretation 3%. It can be concluded that Salauanese likes to get compliment and intimacy contributes in responding compliment